Taṭbīq aṭ-Ṭarīqah al-Mubāsyarah Bi Biṭṭāqah Kwartet Li Tarqiyah Qudrah aṭ-Ṭullāb `Alā at-Ta`bīr asy-Syafawī (Dirāsah Tajrībiyah Bi al-Madrasah al-`Aliyah al-Islāmiyyah Rūḥ al-Falāḥ Samahani) - Nurdina Afrah; Moch. Fajarul Falah; Nur Chalis (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
The subject of the study was "The application of the direct method with the Kwartet card to improve students' ability to express themselves verbally (an experimental study in the Islamic High School Ruhul Falah Samahani)." One of the reasons that encouraged researchers to write this research was problem faced by the teacher because students could not write short sentences that the teacher taught about the subject. They cannot say the sentence he made from the desired material. This arises when researchers choose cards and examples and exercises from easy anecdotal texts, or good phrases that go beyond students' methods and enhance their culture and broaden their circle of knowledge. Researchers believe that students do not understand these subjects because they do not use education methods and education methods that are appropriate for teachers when they teach Arabic, and this causes a lack of desire from them for these subjects. The purpose of writing this thesis is to find out how to improve students' ability to learn Arabic after applying the method directly to the Kwartet card. To obtain data, researchers conducted an experimental study: Quazi Design - Experimental was the first Time-Series Design. In collecting data, researchers make direct observations and tests. As for the community in this study, all students in the Islamic High School Ruhul Falah Samahani 54 students. As for the sample that researchers took, it would be 15 female students. We know from the results of this study that the application of the direct method with a Kwartet card is effective for improving students' ability to express verbally, and this is identical to direct observation with a P = 92.8% which indicates that it falls between the 81-100% limit in very good meaning. The evidence for this is also that the results ("t" test) are greater than the results ("t" tables) and therefore the null hypothesis is valued and alternative hypotheses can be accepted, namely: that the application of the direct method with the Cortette card is effective for improving students' abilities to express in verbal expressions in Arabic lessons at Islamic High School Ruhul Falah Samahani.